UVB LEDs for Medical Phototherapy: LEDs have the potential to become the light source of the future for targeted UVB phototherapy. Issue 5 (9th October 2019) - Seme, Bernd; Streit, Ingolf
Abstract: Phototherapy involves exposure of the skin to light in order to treat various skin diseases such as psoriasis. In the 20th century, great advancements have been made in developing safe and effective narrowband ultraviolet B (NB‐UVB) phototherapy modalities. Targeted phototherapy delivers light exclusively to the affected skin and thereby avoids side effects on unaffected healthy areas. Recently, solid‐state UV light emitting diodes (UV LEDs) have the potential to become the light source of the future for targeted NB‐UVB phototherapy treatments.